80 SMK Jengka 6 students visit UMP - Siti Nurfarmy, Ibrahim (2023)
PEKAN, 27 January 2023 - A total of 80 third- and fourth-graders and eight teachers, accompanied by the Principal of Sekolah Menengah Kebangsaan Jengka 6, Faridzah Ahmad, visited Universiti Malaysia Pahang (UMP) recently.